Defining Summer Gain Among Elementary Students With or at Risk for Reading Disabilities. (July 2019) - Reed, Deborah K.; Aloe, Ariel M.; Reeger, Adam J.; Folsom, Jessica Sidler
Summer reading programs are a form of extended school year services for students in special education. However, previous studies have not reported including high percentages of participants in special education, nor have studies sufficiently controlled for selection bias. This study combined propensity score weighting with partially clustered models to examine the effects of a summer reading program on the growth in reading skills of K–4 students, roughly 50% to 75% of whom were in special education. Results suggest that students in most grades improved on some but not all skills. However, fewer improvements were apparent when participating students were compared with peers via propensity score analyses. In addition, Grade 3 students in the control group outperformed their peers who attended summer school.